Handshake, No. 4 (January 2012) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This issue includes the following headings: mass rapid transit: a tool for urban expansion; financing: beyond sovereign guarantees; and low-income housing: lessons from Latin America.